Implementing UTAUT Model to Analyze Consumer Behaviour in Mobile Recycling Application - Elizabeth Shirley, Stephanie; Santoso, Joan; Kristina, Natalia (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2024)
Abstract—Waste disposal continues to increase globally, causing environmental issues to worsen. Indonesia, with its rapidly growing cities, also struggles to manage all this waste. Numerous mobile applications were released to recycle waste more effectively. However, The rate of mobile recycling application adoption is still low. We contend that lack of awareness and knowledge on recycling is the main cause of low adoption from people, that makes them deny the need for recycling and individual responsibility. Hence, the purpose of this study is to find out if sociopreneur awareness implementation, workshop, on recycling application influence the adoption of recycling applications. TPB and UTAUT model is used to attest the acceptance of workshop on recycling application. Quantitative approach is employed in this study, using a questionnaire of 139 respondents. The structural model is calculated using Smart PLS tools, and the results are validation data. According to the results, the user's intention to use recycling applications with a workshop feature is positively and significantly impacted by four variables (T-Values ≥ 1.96), which are Functional Expectancy, Attemption, Support System, and Perceived Control. While, Society Influence have negative effects (T-Values 1.96) on the user's intention to use recycling applications with a workshop feature.